2017
DOI: 10.1097/aog.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies After the Diagnosis of Mild Gestational Diabetes Mellitus and Risk of Cardiometabolic Disorders

Abstract: Objective To assess the association of subsequent pregnancy with subsequent metabolic syndrome and type II diabetes mellitus after a pregnancy complicated by mild gestational diabetes mellitus (GDM). Methods We conducted a prospective observational follow up study of women with mild GDM randomized from 2002–2007 to usual care or dietary intervention and glucose self-monitoring. Women were evaluated 5–10 years after the parent study. Participants were grouped according to the number of subsequent pregnancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Increased risk of adverse pregnancy outcomes such as the increased risk of developing metabolic syndrome or diabetes, traumatic delivery complications, macrosomia, stillbirths, and congenital anomalies are associated with GDM [35][36][37]. The consequences of GDM for https://doi.org/10.1371/journal.pone.0231096.g002…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of adverse pregnancy outcomes such as the increased risk of developing metabolic syndrome or diabetes, traumatic delivery complications, macrosomia, stillbirths, and congenital anomalies are associated with GDM [35][36][37]. The consequences of GDM for https://doi.org/10.1371/journal.pone.0231096.g002…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) in the adult population is consistently associated with cardiovascular and related diseases . We have recently shown that using the same cohort, women with MetS in pregnancy were at an increased risk for pre‐eclampsia (RR 1.63; 95% CI 1.23–2.15) and gestational diabetes (RR 3.71; 95% CI 2.42–5.67); such pregnancy complications are associated with an increased risk for CVD in adulthood . Our data suggest that MetS may be used to broadly identify women who are at increased risk for delayed fertility, whether they are obese or not.…”
Section: Discussionmentioning
confidence: 74%
“…Second, the long-term prognoses of both mothers and children have not been studied. Pregnant women with GDM are at increased risk for metabolic syndrome (20), type 2 diabetes (21), and cardiovascular disease (22). GDM is also considered to affect future metabolic abnormalities and neurodevelopmental prognoses of children (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%